Group A Streptococcus NAD-Glycohydrolase Inhibits Caveolin 1-Mediated Internalization Into Human Epithelial Cells - Toh, Hirotaka; Lin, Ching-Yu; Nakajima, Shintaro; Aikawa, Chihiro; Nozawa, Takashi; Nakagawa, Ichiro (Frontiers in Cellular and Infection Microbiology, 2019)
Group A Streptococcus (GAS) invades into epithelial cells for persistent infection. GAS has a variety of effector proteins that modulate host systems for their survival in host environments. The main effector proteins of GAS are NAD-glycohydrolase (Nga) and streptolysin O (SLO). Although Nga has NADase activity and shows SLO-dependent cytotoxicity, some clinical isolates harbor NADase-inactive subtypes of Nga, and the function of NADase-inactive Nga is still unclear. In this study, we found that the deletion of nga enhanced the internalization of GAS into HeLa and Ca9-22 cells. Amino acid substitution of Nga R289K/G330D (NADase-inactive) did not enhance GAS invasion, suggesting that Nga may inhibit the internalization of GAS into host cells in a NADase-independent manner. Moreover, double deletion of slo and nga showed similar invasion percentages compared with wild-type GAS, indicating the important role of SLO in the inhibition of GAS invasion by Nga. Furthermore, enhanced internalization of the nga deletion mutant was not observed in Cav1-knockout HeLa cells. Taken together, these findings demonstrated an unrecognized NADase-independent function of Nga as a negative regulator of CAV1-mediated internalization into epithelial cells.